2023
DOI: 10.1111/adj.12997
|View full text |Cite
|
Sign up to set email alerts
|

Vital pulp therapy for permanent teeth with diagnosis of irreversible pulpitis: biological basis and outcome

B Kahler,
NA Taha,
J Lu
et al.

Abstract: Root canal treatment (RCT) has been considered the conventional standard for the management of teeth with carious pulp exposure, particularly in mature teeth presenting with symptoms. Following a better understanding of the histopathology of deep carious lesions, the histology of the cariously exposed pulp and the healing potential of the inflamed pulp, vital pulp therapy (VPT) is increasingly adopted around the world for the management of permanent teeth with clinical signs and symptoms indicative of irrevers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Although the occurrence of pulp canal calcification (PCC) after VPT is recognized as a potential complication 21 , significant calcifications are not expected to occur within a short observation period. While some researchers/clinicians suggest that retreatment of a failed pulpotomy may be perceived as an easier procedure than managing a tooth with filled root canal treatments 22 , the current evidence on the incidence, magnitude, and influential factors of PCC in VPT-treated teeth remains insufficient 21 . Importantly, even if calcification occurs in root canals after VPT, it tends to manifest as canal narrowing rather than complete obliteration, making it generally manageable considering the advancements in endodontic techniques 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the occurrence of pulp canal calcification (PCC) after VPT is recognized as a potential complication 21 , significant calcifications are not expected to occur within a short observation period. While some researchers/clinicians suggest that retreatment of a failed pulpotomy may be perceived as an easier procedure than managing a tooth with filled root canal treatments 22 , the current evidence on the incidence, magnitude, and influential factors of PCC in VPT-treated teeth remains insufficient 21 . Importantly, even if calcification occurs in root canals after VPT, it tends to manifest as canal narrowing rather than complete obliteration, making it generally manageable considering the advancements in endodontic techniques 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Accurate diagnosis of pulp inflammatory status before treatment could affect the results of pulpotomy. However, several studies have reported the successful outcome of VPT for irreversible pulpitis [14,25,26], and this would exclude misdiagnosis of pulp inflammation from the causes of pulpotomy failure.…”
Section: Discussionmentioning
confidence: 99%
“…There is still general doubt on classifying pulpitis (irreversible, partial irreversible, reversible) when the histological findings do not meet the symptoms or signs that the patient presents with. [23,24].…”
Section: Diagnosismentioning
confidence: 99%